Analisis Kualitas Produk, Kualitas Pelayanan dan Penggunaan Digital Marketing terhadap Tingkat Kepuasan Konsumen pada Humble Espresso Kota Denpasar - Wiratama, Nyoman Indra; Hartiati, Amna; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 2 (2021): JuniDO - 10.24843/JRMA.2021.v09.i02.p10, 2021)
The purpose of this research is to know the effect of the use of digital marketing conducted by Humble Espresso in Denpasar City. Knowing the attributes of products and services that are considered important by consumers to achieve customer satisfaction with the quality of products and services. Calculating the performance and level of customer satisfaction to the quality of service. Specify the attributes that need to get priority improvements. This study uses the Importance Performance Analysis (IPA) analysis method. Sampling using Slovin and Lemeshow formulation method with the number of respondents as many as 86 respondents at Humble Espresso and 100 respondents for the spread of external questionnaires in Denpasar. The results showed that the influence of digital marketing that has been done by Humble Espresso is customers like the content displayed on Humble Espresso Instagram media in the form of photos, videos, or instastory that has an impact on the increasing customer buying interest. The most important product and service attributes that Humble Espresso has to achieve customer satisfaction is the friendliness of employee attitude with the highest score of 401. Attributes with the highest level of performance in the quality of service is good communication ability by obtaining the highest score of 388, attributes with the highest satisfaction level on the quality of service is modern equipment by obtaining the highest satisfaction level of 101%. Attributes that become the priority of improvement in Humble Espresso based on the analysis of IPA method is a comfortable room, the willingness of employees to respond quickly to customer complaints, the ability of employees to serve customer complaints quickly, the suitability of prices with product quality, and affordable prices. Keyword: digital marketing, product quality, service quality, and customer satisfaction